2012
DOI: 10.4028/www.scientific.net/amr.594-597.1324
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Analysis of Underground Concrete Arch Structure Strengthened with Near-Surface Bonded CFRP Strips

Abstract: To strengthen underground arch structure, the method with near-surface bonded carbon fiber reinforced polymer (CFRP) strips is proposed. A nonlinear finite element program is built to analyze concrete arch structure strengthened with CFRP. Factors that influence the strengthening effect are discussed. After arch strengthened with near-surface bonded CFRP strips, the cracking load, the yield load and the ultimate load has been greatly improved, the stiffness has also been greatly improved. The bearing capacity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
(5 reference statements)
0
1
0
Order By: Relevance
“…Fiber reinforced polymers have also been used to reinforce and strengthen arches. Numerous experimental and numerical studies were performed on the FRP strengthening masonry or concrete arches, shells and vaults and confirmed the efficiency of the FRP strengthening systems (Ali and Hamza, 2015; Avorio and Borri, 2001; Bati et al, 2013; Cao et al, 2010; Chen et al, 2011, 2015; Fagone et al, 2018; Flaga and Kwiecien, 2010; Jiang et al, 2012; Liu et al, 2020; Meier et al, 2011; Oliveira et al, 2010; Wang et al, 2011, 2017, 2018, 2019; Xie et al, 2014; Zhang et al, 2015; Zhao et al, 2021). Firat and Eren (Firat and Eren, 2015) found that the capacity of damaged masonry arch strengthened with FRP increases at least 58% in comparison with unstrengthen masonry arches and strengthening of joints with epoxy resin is an effective alternative to increase the damaged masonry arch capacity.…”
Section: Introductionmentioning
confidence: 83%
“…Fiber reinforced polymers have also been used to reinforce and strengthen arches. Numerous experimental and numerical studies were performed on the FRP strengthening masonry or concrete arches, shells and vaults and confirmed the efficiency of the FRP strengthening systems (Ali and Hamza, 2015; Avorio and Borri, 2001; Bati et al, 2013; Cao et al, 2010; Chen et al, 2011, 2015; Fagone et al, 2018; Flaga and Kwiecien, 2010; Jiang et al, 2012; Liu et al, 2020; Meier et al, 2011; Oliveira et al, 2010; Wang et al, 2011, 2017, 2018, 2019; Xie et al, 2014; Zhang et al, 2015; Zhao et al, 2021). Firat and Eren (Firat and Eren, 2015) found that the capacity of damaged masonry arch strengthened with FRP increases at least 58% in comparison with unstrengthen masonry arches and strengthening of joints with epoxy resin is an effective alternative to increase the damaged masonry arch capacity.…”
Section: Introductionmentioning
confidence: 83%